Discussions on Universal Conscription and the “Professional Army” in Russian and World Military Literature of the Late XIX - First Half of the XX Centuries - A. A. Chernilovsky (Научный диалог, 2019)
The article is devoted to the discussion of the transition from the mass to the professional army, which was conducted in the domestic and world military literature both before the First World War and in the period between the World Wars. The relevance of the study is due to the fact that in our time, the transition to a professional army really takes place in many countries of the world, including Russia. A review is made of a number of military works, the authors of which upheld the idea of a professional army. The content of the concepts of the White Immigrant General Gerua and the German General Seeckt is analyzed in particular detail. It is concluded that the understanding of a professional army in the first half of the 20th century was fundamentally different from the modern one: its supporters believed that it should not be a replacement, but just a supplement to the mass conscript army, a kind of guard of the industrial era. Particular attention is paid to criticism of the concept of a professional army by Soviet military authors of the 1920s and 1930s, including the People’s Commissar for Defense Marshal Voroshilov, as well as some foreign military authors of that time. The article shows that this criticism was justified: the Second World War was conducted by draft armies.